Perspectives on yellowing in the degradation of polymer materials: inter-relationship of structure, mechanisms and modes of stabilisation. (July 2022) - Allen, Norman S.; Edge, Michele; Hussain, Sajid
Highlights: Presents an expert perspective on the phenomenon of yellowing in the manufacture and processing degradation of polymer materials. Structural and stability relationships are described for thermal stabilisers confirming the role of quinone-imine and methide formation. Origin of yellowing processes described for a range of aromatic and aromatic amine polymers. Conventional and unconventional methods of inhibition of the yellowing processes are provided. Abstract: In the formulation or processing and post-use of polymer materials, one of the most important facets giving significant concern to the polymer industry is that of discolouration or more specifically the "Yellowing" phenomenon. Although the literature is abundant covering various aspects of this problem it can be what one may describe as a serious "bug" in the progress of many polymer applications and indeed can limit their acceptance in many products. These may be in clear films and bottles, white goods or recycling and post-use where heat and light can discolour polymer materials. The science underpinning the yellowing can be due to the additives, more importantly, the phenolic/amine antioxidants and/or inherent in the polymers themselves especially polyaromatics such as polyesters or polycarbonates, epoxy-amines, and polystyrene to name but a few. In many industrial applications solving or overcoming this issue is not always easy and can be problematic. The chemistry of these processes will be discussed and highlighted and effective modes of stabilisation and/or inhibition presented with often unconventional detailed examples and their structural developments for optimisation of additive performance. Thus, examples of chemical treatment processes to minimise polymer yellowing will also be presented where polyglycols and various chemical reducing agents provide some useful ideas. Hopefully, a clearer understanding of the types of chemistries involved in yellowing and their minimisation will provide a useful way forward for the polymer and additive manufacturers and technologists in unravelling and solving their potential issues and problems at many of the stages of polymer manufacture and processing.